Localized synchronous acquired post-radiotherapy melanocytic nevi. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2013)
Was first observed a 41-year-old man who when aged 37 had undergone surgery due to liposarcoma located in the sartorius muscle of the right thigh. Histological examination had led to the diagnosis of differentiated liposarcoma. After surgery, the patient reported having performed radiotherapy on the right thigh. Reason of the dermatological consultation was the presence of numerous melanocytic nevi on the right thigh appeared all together several months after discontinuation of radiotherapy. The dermatological examination showed a surgical scar which affected longitudinally large part of the right thigh. There were also superficial telangiectasias and twelve melanocytic nevi of 1-2 mm in diameter, while on the same region of the left thigh there were only 3 acquired melanocytic nevi.